2014
DOI: 10.1111/avsc.12152
|View full text |Cite
|
Sign up to set email alerts
|

Managing cattle grazing and overstorey cover for the conversion of pine monocultures into mixedMediterranean woodlands

Abstract: Question: A large proportion (70%) of coniferous forest area in Israel is used for livestock grazing. Recently, the possibility of managing these monospecific plantations to form mixed conifer-broad-leaved woodlands via natural regeneration processes has been considered. In light of this we pose the question, how does the interaction of cattle grazing and overstorey thinning (hereafter, thinning) affect natural regeneration in east Mediterranean pine plantations?Location: Menashe region, Mediterranean Israel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…grazing being more frequent in the northern forests and mixed sheep and goat grazing more typical of the southern ones. Forests located in the central part of Israel were usually less intensively grazed (Osem et al, 2015). In this study, we assume that grazing had relatively comparable effect on forest structure and thus on catchment water budget in the forested catchments of our study region.…”
Section: The Forest Sitesmentioning
confidence: 98%
“…grazing being more frequent in the northern forests and mixed sheep and goat grazing more typical of the southern ones. Forests located in the central part of Israel were usually less intensively grazed (Osem et al, 2015). In this study, we assume that grazing had relatively comparable effect on forest structure and thus on catchment water budget in the forested catchments of our study region.…”
Section: The Forest Sitesmentioning
confidence: 98%
“…In parallel with broad-scale changes in herbivore populations, local effects can cascade to regional trends in biodiversity [18] and include development of new, relatively stable alternative states of some ecosystems [5,19,20]. Thus, herbivory is highly important for the maintenance of forest habitat values, including structural and compositional heterogeneity, as well as biodiversity [12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study within the same system, we found the effect of overstory thinning and grazing on tree recruitment in the forest understory to depend on sapling size. While smaller saplings (<20 cm in height) were generally more abundant in grazed non-thinned areas, larger saplings were more abundant in the ungrazed-thinned areas (Osem et al 2015). Higher frequency of tree and shrub species in the understory of non-thinned plots may be related to better seedling establishment of large seeded woody species such as Q. calliprinos, S. officinalis, and Phillyrea latifolia resulting from facilitative effects of the overstory (Alon and Kadmon 1996) and related ground litter layer (Sayer 2006).…”
Section: Understory Community Structurementioning
confidence: 95%
“…Previous studies looking at the understory in East Mediterranean pine plantations have focused primarily on natural regeneration of tree species (Osem et al 2009(Osem et al , 2013(Osem et al , 2015. In this study we pursued a more comprehensive understanding of the ways by which understory structure and function is driven by management factors.…”
Section: Introductionmentioning
confidence: 99%